The biomechanics of jumping: The relevance to field event athletes - Burnett, A. (coachesinfo.com)
The progression of exercises for an field event athlete therefore, might be: General Preparation - Choose jumping exercises that have larger contact times and develop both concentric and eccentric strength, the components of elastic strength. You may develop eccentric strength via jumping down from obstacles such as a steeplechase hurdle or boxes and concentric strength may be developed via incline bounding and stair jumps. Jumps with a weighted jacket may also develop eccentric and concentric strength. As the volume of jumping continually increases in this phase, most of these exercises could be done grass rather than an artificial track surface. Also, two-legged jumps are less stressful on the body than one-legged jumps, so a greater volume of these could be done. Specific Preparation - This is the period of the year where most athletes get injured as both volume and intensity are relatively high. Faster one-legged jumping exercises such as bounding and hopping would decrease contact times. This could be done by increasing the approach speed into the series of jumps. Box jumps emphasising fast rebound would be a good option in this phase of training. The athlete also needs to think about start progressing to harder surfaces. Ground reaction forces are higher so volume has to start decreasing. The amount of double-legged jumps may also decrease. Competition Season - The main emphasis in training should be on exercises that produce the most specific adaptations. For example, the proportion of technical jumps by all jumpers should at their highest. For throwers, the contact times should be decreased so that the exercises meet the demands of their specific event.